BIBAC and TAC clones containing potato genomic DNA fragments larger than 100 kb are not stable in Agrobacterium - Song, J.; Bradeen, J.M.; Naess, S.K.; Helgeson, J.P.
Development of efficient methods to transfer large DNA fragments into plants will greatly facilitate the map-based cloning of genes. The recently developed BIBAC and TAC vectors have shown potential to deliver large DNA fragments into plants via Agrobacterium-mediated transformation. Here we report that BIBAC and TAC clones containing potato genomic DNA fragments larger than 100 kb are not stable in Agrobacterium. We tested the possible factors that may cause instability, including the insert sizes of the BIBAC and TAC constructs, potato DNA fragments consisting of highly repetitive or largely single-copy DNA sequences, different Agrobacterium transformation methods and different Agrobacterium strains. The insert sizes of the potato BIBAC and TAC constructs were found to be critical to their stability in Agrobacterium. All constructs containing a potato DNA fragment larger than 100 kb were not stable in any of the four tested Agrobacterium strains, including two recA deficient strains. We developed a transposon-based technique that can be used to efficiently subclone a BAC insert into two to three BIBAC/TAC constructs to circumvent the instability problem.
Keywords: BAC; BIBAC; TAC; AGROBACTERIUM; PLANT TRANSFORMATION